Influence of power and maximal strength training on thermal reaction and vertical jump performance in Brazilian basketball players: a preliminary study - Corte Jaime Della; Pereira Wendell Luiz M.; Corrêa Eduardo Emil Lacerda S.; de Oliveira João Gabriel Miranda; Lima Bruno Lucas Pinheiro; de Castro Juliana Brandão Pinto; Lima Vicente Pinheiro (Sciendo, 2020)
Study aim: To evaluate the effect of power and muscle strength training on skin temperature and the performance of the vertical jump with countermovement (CMJ).